2016
DOI: 10.3171/2016.5.focus16145
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with improved survival following surgery for renal cell carcinoma spinal metastases

Abstract: OBJECTIVE Renal cell carcinoma (RCC) frequently metastasizes to the spine, causing pain or neurological dysfunction, and is often resistant to standard therapies. Spinal surgery is frequently required, but may result in high morbidity rates. The authors sought to identify prognostic factors and determine clinical outcomes in patients undergoing surgery for RCC spinal metastases. METHODS The authors searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…[1][2][3] For example, surgical resection may lead to organ failure and rapid tumor metastasis; radiotherapy has toxic effects on normal tissues, and non-specific chemotherapy leads to severe systemic toxicity. [4][5][6] As a result, modern medical research has focused on the urgent development of newer, less toxic treatment methods. In recent years, photothermal therapy (PTT) has been demonstrated as a highly effective cancer treatment by many scientists.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For example, surgical resection may lead to organ failure and rapid tumor metastasis; radiotherapy has toxic effects on normal tissues, and non-specific chemotherapy leads to severe systemic toxicity. [4][5][6] As a result, modern medical research has focused on the urgent development of newer, less toxic treatment methods. In recent years, photothermal therapy (PTT) has been demonstrated as a highly effective cancer treatment by many scientists.…”
Section: Introductionmentioning
confidence: 99%
“…The 338 full texts were excluded with the following reason: 304 studies didn ’ t involve prognostic effect of the factors involved in Tokuhashi Score; 28 studies were literature or systematic reviews; 3 studies of Lei [1618] used repeated patients cohort, thus only the one [18] identified primary tumor histology as non-small cell lung cancer(NSCLC) was included; and another 4 studies of Rades [1922] were also excluded for using repeated patients cohorts with other studies. Finally, 63 studies [6, 8, 9, 18, 2472, 7482] with 10,411 participants and 38 studies [8, 9, 18, 26, 2838, 40, 41, 43, 44, 46, 47, 49, 5153, 56, 58, 60, 63, 64, 66, 69, 71, 76, 78–81] with 7462 participants were included in the qualitative and quantitative synthesis respectively.
Fig. 1Flowchart of studies identification and selection
…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 1440 unique results, where 47 articles met the inclusion criteria with a total of 807 patients included in the data analysis ( Figure 1 ). 1 , 10 , 11 , 13 , 15 , 18 60 Demographics, presenting features, treatment, and survival information were compiled for those patients with known status. The majority of patients were male (75.5%), and the mean age at diagnosis of RCC spine metastasis was 56.7 years.…”
Section: Resultsmentioning
confidence: 99%